Pengaruh Budaya Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Surya Terang Teknik Abadi Kota Tangerang - Annisa, Gustin Nur; Nurhadi; Hadi , Seno Sudarmono (CV Warnak Johanna Nusantara, 2026)
Abstracts - This study aims to explain the influence of work culture and work discipline on employee performance at PT Surya Terang Teknik Abadi, Tangerang City. The population in this study were employees of PT Surya Terang Teknik Abadi, Tangerang City. Using a quantitative method with a saturated sample of 35 employees, data were collected through questionnaires and analyzed using IBM SPSS version 25. The results of the study showed that partially, work culture (X1) and work discipline (X2) both had a positive and significant effect on employee performance. This is evidenced by the t- value of work culture (2.698) and work discipline (4.559) which are greater than t- table (2.046), and the sig. value (0.000) which is less than 0.05. Simultaneously, work culture and work discipline have also been shown to have a positive and significant effect on employee performance (Y). This is indicated by the F-value of 109.725 which exceeds F-table 3.29. The R Square value of 87.3% indicates that these two variables together make a major contribution to employee performance. Meanwhile, the remaining 12.7% was influenced by other factors not examined in this study.